2015
DOI: 10.5507/bp.2015.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of novel 7-MEOTA-donepezil like hybrids and N-alkylated tacrine analogues in the treatment of quinuclidinyl benzilate-induced behavioural deficits in rats performing the multiple T-maze test

Abstract: Aims. The number of approved drugs for the clinical treatment of Alzheimer disease remains limited. For this reason, there is extensive search for novel therapies. Of these, cholinesterase inhibitors have some proven benefit in slowing the disease progression and still remain the first-line therapeutic approach. In this study, the pro-cognitive effect of four novel tacrine-related inhibitors was evaluated and compared with the standards, tacrine and donepezil. Methods. Wistar rats trained to perform the multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Such an orientation of THA scaffold is highly consistent with other recently described THA dual binders like tacrine-tianeptine or 7-methoxytacrine-adamantylamine heterodimers [ 65 , 66 , 67 ]. On contrary, it has to be stated that opposite orientation, i.e., THA lodging within PAS region, can be also found in the literature like in 7-methoxytacrine- p -anisidine, tacrine-Trolox or 7-methoxytacrine-donepezil like compounds [ 68 , 69 , 70 ]. In case of K1383 , the 6-Cl-THA moiety is facing Trp86 (4.1 Å) in a π-π/cation-π parallel manner.…”
Section: Resultsmentioning
confidence: 99%
“…Such an orientation of THA scaffold is highly consistent with other recently described THA dual binders like tacrine-tianeptine or 7-methoxytacrine-adamantylamine heterodimers [ 65 , 66 , 67 ]. On contrary, it has to be stated that opposite orientation, i.e., THA lodging within PAS region, can be also found in the literature like in 7-methoxytacrine- p -anisidine, tacrine-Trolox or 7-methoxytacrine-donepezil like compounds [ 68 , 69 , 70 ]. In case of K1383 , the 6-Cl-THA moiety is facing Trp86 (4.1 Å) in a π-π/cation-π parallel manner.…”
Section: Resultsmentioning
confidence: 99%
“…A similar stereochemical orientation has also been reported for tacrine-tianeptine or 7-methoxytacrine-adamantylamine hybrids (Ceschi et al 2016;Spilovska et al 2013;Korabecny et al 2015). An opposite arrangement, in which tacrine interacts with PAS has been reported for 7-methoxytacrine-p-anisidine (Korabecny et al 2015), 7-methoxytacrine-donepezil (Misik et al 2015) and tacrine-trolox heterodimers (Nepovimova et al 2015). p-Anisidine is known to suppress intracellular accumulation of the precursor to the neurotoxic Aβ, APP.…”
Section: Multifunctional Drugs Containing Metal-chelating and Oxidatimentioning
confidence: 95%
“…These compounds as reversible AChE inhibitors have also other anticholinergic effects; in vitro and ex vivo experiments showed that they can inhibit also nicotinic (nAChR) and muscarinic cholinergic receptors (mAChR) of both peripheral and central types . Thus, these compounds may also diminish the effect of cholinergic receptor overstimulation during organophosphate poisoning . The potential pharmacodynamic effects were described but in vivo pharmacokinetic parameters of the compounds are still missing in the literature.…”
Section: Resultsmentioning
confidence: 99%